The singularities - Banville, John (Alfred A. Knopf, 2022)
"From the revered, Booker Prize-winning author comes a playful, multi-layered novel of nostalgia, life and death, and quantum theory, which opens with the return of one of his most celebrated characters-Freddie Montgomery from The Book of Evidence-as he is released from prison. A man with a borrowed name steps from a flashy red sportscar-also borrowed-onto the estate of his youth. But all is not as it seems. There is a new family living in the drafty old house: the Godleys, descendants of the late, world-famous scientist Adam Godley, whose theory of existence threw the universe into chaos. And this mystery man, who has just completed a prison sentence, feels as if time has stopped, or was torn, or was opened in new and strange ways. He must now vie with the dysfunctional Godley family, with their harried housekeeper who becomes his landlady, with the recently commissioned biographer of Godley Sr., and with a wealthy and beautiful woman from his past who comes bearing an unusual request. With sparkling intelligence and rapier wit, John Banville revisits some of his career's most memorable characters, in a novel as mischievous as it is brilliantly conceived. The Singularities occupies a singular space and will surely be one of his most admired works"--